Comorbidity Patterns of Psychiatric Conditions in Canadian Armed Forces Personnel. (July 2019) - Richardson, J. Don; Thompson, Amanda; King, Lisa; Ketcheson, Felicia; Shnaider, Philippe; Armour, Cherie; St. Cyr, Kate; Sareen, Jitender; Elhai, Jon D.; Zamorski, Mark A.
Objective: Posttraumatic stress disorder (PTSD) is often accompanied by other mental health conditions, including major depressive disorder (MDD), substance misuse disorders, and anxiety disorders. The objective of the current study is to delineate classes of comorbidity and investigate predictors of comorbidity classes amongst a sample of Canadian Armed Forces (CAF) Regular Force personnel. Methods: Latent class analyses (LCAs) were applied to cross-sectional data obtained between April and August 2013 from a nationally representative random sample of 6700 CAF Regular Force personnel who deployed to the mission in Afghanistan. Results: MDD was the most common diagnosis (8.0%), followed by PTSD (5.3%) and generalized anxiety disorder (4.7%). Of those with a mental health condition, LCA revealed 3 classes of comorbidity: a highly comorbid class (8.3%), a depressed-only class (4.6%), and an alcohol use–only class (3.1%). Multinomial logit regression showed that women (adjusted relative risk ratio [ARRR] = 2.77; 95% CI, 2.13 to 3.60; P < 0.01) and personnel reporting higher trauma exposure (ARRR = 4.18; 95% CI, 3.13 to 5.57; P < 0.01) were at increased risk of membership in the comorbid class compared to those without a mental health condition. When compared to those with no mental health condition, experiencing childhood abuse increased the risk of being in any comorbidity class. Conclusions: Results provide further evidence to support screening for and treatment of comorbid mental health conditions. The role of sex, childhood abuse, and combat deployment in determining class membership may also prove valuable for clinicians treating military-related mental health conditions.